To complete the square for the equation \( x^2 + 8x = 9 \), we start by rearranging the equation:
-
Move the constant to the other side: \[ x^2 + 8x - 9 = 0 \]
-
To complete the square, we need to take the coefficient of \( x \) (which is 8), divide it by 2 (getting 4), and then square that value: \[ \left( \frac{8}{2} \right)^2 = 4^2 = 16 \]
-
Now, add and subtract this value on the left side of the equation: \[ x^2 + 8x + 16 - 16 - 9 = 0 \]
-
Simplify the left side: \[ (x + 4)^2 - 25 = 0 \]
-
Move the constant term to the right side: \[ (x + 4)^2 = 25 \]
-
Take the square root of both sides, remembering to consider both the positive and negative roots: \[ x + 4 = 5 \quad \text{or} \quad x + 4 = -5 \]
-
Solving these two equations gives us: \[ x + 4 = 5 \quad \Rightarrow \quad x = 5 - 4 = 1 \] \[ x + 4 = -5 \quad \Rightarrow \quad x = -5 - 4 = -9 \]
Thus, the two values that solve the equation \( x^2 + 8x = 9 \) are: \[ \boxed{1} \quad \text{and} \quad \boxed{-9}. \]